Aluminum Dreams: The Making of Light Modernity - Sheller (MIT Press, 2014)
Monograph
fulltext
Keywords: Engineered Materials, Dielectrics and Plasmas; Components, Circuits, Devices and Systems; General Topics for Engineers; Transportation; Power, Energy and Industry Applications; Aerospace